2019
DOI: 10.3390/met9121332
|View full text |Cite
|
Sign up to set email alerts
|

Animal Origin Bioactive Hydroxyapatite Thin Films Synthesized by RF-Magnetron Sputtering on 3D Printed Cranial Implants

Abstract: Ti6Al4V cranial prostheses in the form of patterned meshes were 3D printed by selective laser melting in an argon environment; using a CO2 laser source and micron-sized Ti6Al4V powder as the starting material. The size and shape of prostheses were chosen based on actual computer tomography images of patient skull fractures supplied in the framework of a collaboration with a neurosurgery clinic. After optimizations of scanning speed and laser parameters, the printed material was defect-free (as shown by metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…3D cranial meshes of Ti6Al4V were successfully manufactured using SLM and coated using radio-frequency magnetron sputtering with a~600-nanometer layer of hydroxyapatite that was derived from biogenic sustainable resources (i.e., calcined cortical bovine bones). The Bio-HA sputtered films elicited promising biological performances [9].…”
Section: Contributionsmentioning
confidence: 99%
“…3D cranial meshes of Ti6Al4V were successfully manufactured using SLM and coated using radio-frequency magnetron sputtering with a~600-nanometer layer of hydroxyapatite that was derived from biogenic sustainable resources (i.e., calcined cortical bovine bones). The Bio-HA sputtered films elicited promising biological performances [9].…”
Section: Contributionsmentioning
confidence: 99%
“…It showed that they could be used for load-bearing implants such as hip, knee and shoulder joints [ 151 , 152 ]. Moreover, orthopedic bone prototypes and meshed cranial prostheses implants were successfully developed for biomedical applications [ 57 , 153 , 154 ].…”
Section: Metal Matrix Composites (Mmcs)mentioning
confidence: 99%
“…The PLD coated samples were immersed in 1 mL of the same cell culture medium (i.e., DMEM supplemented with 10% fetal bovine serum), used in the case of the cytocompatibility assay, detailed here-under. Recent developments have indicated that a more truthful evaluation of the degradation speed/biomineralization capacity of a material can be achieved by testing under cell culture media, and not in the simplistic simulated body fluids such as Tris-HCl or Kokubo SBF, since the cell culture media reproduces with higher accuracy the composition of the intercellular medium [59,64,79]. The solubility/bioactivity in vitro tests were carried out in a dedicated biological incubator under homeostatic conditions (i.e., humidified atmosphere, temperature of 37 • C, and partial pressure of CO 2 of 5 kPa) for different time periods of 1, 3, and 7 days, respectively.…”
Section: Solubility/bioactivity Tests Under Biomimetic Conditionsmentioning
confidence: 99%